E-076 Outcomes of large vessel occlusion thrombectomy in patients with CT perfusion defined large core stroke. (4th August 2020) - Aghaebrahim, A; Desai, S; Monteiro, A; Granja, M; Agnoletto, G; Cortez, G; Gonsales, D; Legault, C; Powers, C; Jadhav, A; Sauvageau, E; Albers, G; et al.
Abstract : Introduction: The benefit of endovascular thrombectomy (ET) is well established in patients with small anterior circulation infarctions and large penumbra. However, this benefit is not proven in patients with a baseline large core infarction. This subpopulation was excluded from major thrombectomy clinical trials. The purpose of this study was to report the outcome of patients with large baseline core based on CTP who underwent stroke thrombectomy at 4 large stroke centers. Methods: Prospectively collected large vessel occlusion databases were queried to identify patients with large baseline infarct cores (CBF greater than 30% ≥ 50 mL; based on Computed Tomography Perfusion [CTP] processed by RAPID Software [iSchemaView]). All patients treated with thrombectomy were included in the study. Modified Rankin Scale (mRS) was used for evaluation of clinical outcomes at baseline and 90 days. Demographic information, baseline clinical data, radiological features (infarct core size, penumbra and collaterals) and follow-up were collected. Results: A total of 75 patients were included in the study. Mean age was 65 ±14.9 years and 45.3% were male. Median infarct core was 75.5 mL (IQR 39) and median ASPECTS was 7 (range 3–10). Close to half (50.7%) of patients received IV tPa. Only 8.3% of patients had good collaterals. Mean time to groin puncture was 373±384 minutes and 88% of patients achieved TICI 2b or higher. Rates of good outcome (mRS 0–2) and acceptable outcome (mRS 0–3) were 28.4% and 35.5% respectively. Rate of Parenchymal Hematoma type 2 was 10.6%. The rate of good outcome was significantly higher in patients treated <6h (44.2% vs. 17.4%, P=0.023). Conclusions: Acute stroke thrombectomy may be beneficial in some patients with large core based on CTP especially those who present early (<6 hours from last seen well) and it should not be withhold solely based on the estimated core infarct volume on CTP. Disclosures: A. Aghaebrahim: None. S. Desai: None. A. Monteiro: None. M. Granja: None. G. Agnoletto: None. G. Cortez: None. D. Gonsales: None. C. Legault: None. C. Powers: None. A. Jadhav: None. E. Sauvageau: None. G. Albers: 5; C; CEO of RAPID Software (iSchema View). T. Jovin: None. R. Hanel: 2; C; Microvention, Codman, Stryker, Medtronic.